Absolute quantification of myocardial blood flow with constrained estimation of the arterial input function. Issue 3 (31st January 2013) - Fluckiger, Jacob U.; Benefield, Brandon C.; Harris, Kathleen R.; Lee, Daniel C.
<x xml:space="preserve">Abstract</x> Purpose: To evaluate the performance of the constrained alternating minimization with model (CAMM) method for estimating the input function from the myocardial tissue curves. Materials and Methods: Myocardial perfusion imaging was performed on seven canine models of coronary artery disease in 15 imaging sessions. In each session, stress was induced with intravenous infusion of adenosine and a variable occluder created coronary artery stenosis. A dual bolus protocol was used for each acquisition, and input functions were then estimated using the CAMM method with data acquired from the high dose scan following each imaging session. For each acquisition, myocardial blood flow was measured by injected microspheres. Results: The dual bolus and CAMM‐derived flows were not significantly different (P = 0.18), and the correlation between the two methods was high (r = 0.97). The correlation between the dual bolus and CAMM methods and microsphere measurements was lower than that for the two MR methods (r = 0.53; r = 0.43, respectively). Conclusion: The CAMM method presented here shows promise in estimating myocardial blood flow in patients with coronary artery disease at stress with a single injection and without any specialized acquisitions. Further work is needed to validate the approach in a clinical setting. J. Magn. Reson. Imaging 2013;38:603–609. © 2013 Wiley Periodicals, Inc.